Analysis of Natural Resource Potential in Ciwaru Village, Sukabumi Regency, as a Basis for Ecotourism Development - Zuraydha Juaeni Putri; Michele Yudith Hapsari Lumbanraja; Kaiyya Maura Nadhifa (Pravda: Social Science Interdisciplinary Journal, 2026)
Background. Ciwaru Village, located in Sukabumi Regency, has significant natural resource potential for development as an ecotourism area. Its natural beauty, agricultural sector, and local culture are attractions that can support the development of environmentally-based tourism. Furthermore, the presence of a river with clean, clear water offers opportunities for sustainable water tourism development. Purpose. This study aims to identify potential resources that can be developed into ecotourism in Ciwaru Village and to analyze the condition of supporting infrastructure available in the village. Method. This research used a qualitative method with a literature review approach. Data were obtained from various literature, documents, and written sources relevant to village potential and ecotourism development. Results. The research results show that Ciwaru Village has potential natural resources, including water resources, agriculture, and local culture. The river, with its clean and clear water, has been utilized by the community for water tourism activities such as white-water rafting. Local agricultural and cultural potential can also be developed as additional attractions within an integrated ecotourism concept. Conclusion. Ciwaru Village has significant potential for development as an ecotourism destination based on natural resources and community participation. This development requires support from infrastructure improvements and sustainable planning to deliver economic benefits without compromising environmental sustainability and local culture.